Expression and effect of P38 mitogen-activated protein kinase and transforming growth factor-β in gastric cancer - YANG Lu, LI Zixin, CHANG Jianlan (Zhongguo linchuang yanjiu)
Gastric cancer is the most common malignant tumors in the upper digestive tract in the world. Although there are many treatment methods such as endoscopic resection, surgery, chemotherapy, targeted therapy, immunotherapy and combination therapy, the overall survival rate of patients with gastric cancer is still at a low level. This paper explores related tumor molecular markers of gastric cancer ［P38 mitogen-activated protein kinase (P38 MAPK),transforming growth factor-β(TGF-β)］, and summarizes the research progress of their expression and function in gastric cancer, which may provide new ideas for the treatment of gastric cancer, investigate new targeted drugs, and ultimately improve the prognosis of patients with gastric cancer.